Desenvolvimento de protótipo de cadeira de banho para indivíduos com paralisia cerebral tetraparética espástica - Dutra, Fabíola Canal Merlin (2008)
This study proposes to develop an equipment that attends the demands of tetraplegic people due to cerebral palsy and that promotes an adequate caregivers postural biomechanics during the shower activity of daily living. First, a bibliographic review was performed to define the terms refering to cerebral palsy, activity of daily living (specifically shower), and assistive technology, besides listing the wheelchairs made on the mainly national assistive technology companies. Therefore, this is a descriptive-exploratory study based on a literature review and on a based-field exploration research. On the field research a survey was adopted as a methodological procedure as it is related to a direct investigation related to a phenomenon, on the case, represented by the current shower situation of the people investigated in this study. Data were collected with the application of a form to the caregivers and consumers of the medical-therapeutic treatment and place used by the participants. Such form, which was made up of open and close questions, tried to identify, besides the personal data of evaluated users and consumers, the characteristics of the current shower activity, such as the place where it takes place in the house, the used equipmentS, in the case there is any, and how often it occurs. The form also was used to identify the caregivers and consumers desires and perceptions in relation to the present characteristics of the new dispositive besides the users and consumers anthropometric data. The evaluation of the results obtained through the form, together with the practice and clinical experience of the researchers and engineers involved in this study, made it possible to develop and make up a real shower chair prototype with the specific adjusts destined to adequate the equipment to be used according to the needs of each user and consumer